Canadian monetary, banking, and fiscal development - McIvor, R. Craig (Toronto : Macmillan Co. of Canada, 1958)
This book discusses the history of monetary, banking and fiscal development in Canada. It also highlights the lessons learnt from the monetary difficulties in New France as well as early currency and exchange in British North America.
Includes index.
Includes bibliographical references: p. 253-256
usc 25/07/2017
Loans
Keywords: Finance; Banks and banking; Currency question; Fiscal policy; Canada